Logistics in Estonian business companies - Kiisler, Ain (Transport, 2008)
The article describes logistics survey in Estonia carried out in 2007 as a part of the LogOnBaltic project. The level of logistics in Estonian manufacturing, trading and logistics companies is explored through logistics costs, performance indicators, outsourcing, ICT use and logistics self‐estimation of the companies responded. Responses from 186 Estonian companies were gathered through a web‐based survey (38% of manufacturing, 38% of trading and 24% of logistics sector). Logistics costs as the percentage of turnover make in average 13.8% in manufacturing and 13.3% in trading. Transportation and inventory carrying cost form around 70% of overall logistics costs. Considering the logistics indicators surveyed, Estonian companies show up with relatively low perfect order fulfillment rates, short customer order fulfillment cycles and effective management of cash flows. The most widely outsourced logistics function is international transportation followed by domestic transportation, freight forwarding and reverse logistics. By 2010, the outsourcing of IT systems in logistics followed by inventory management, warehousing and product customization is expected to increase more substantially. The awareness of logistics importance is still low among Estonian companies. Only 27–44% of those agree that logistics has a considerable impact on profitability, competitive advantage, top management or customer service level.First published online: 27 Oct 2010